Cu-Li2MnSiO4-polyaniline composite hybrids as high performance cathode for lithium batteries - Lee, Sol-Nip; Baek, Seulgi; Amaresh, Samuthirapandian; Aravindan, Vanchiappan; Chung, Kyung Yoon; Cho, Byung Won; Yoon, Won-Sub; Lee, Yun-Sung (ELSEVIER SCIENCE SA, 2015)
We reported the dramatic improvement in electrochemical properties of high capacity orthosilicate, Li2MnSiO4 by conventional sol-gel route. Simple inclusion of metallic Cu and subsequent hybridization with polyaniline (PANI) nanofibers certainly promotes superior electrochemical activity in terms of high reversibility i.e. beyond one electron reaction and cycling stability. First, the Li2MnSiO4 nanoparticles are prepared by adipic acid assisted sol-gel technique at 700 degrees C under Ar flow by fine tuning the sintering duration. Then, optimization of adipic acid and Cu concentrations are performed based on the mentioned sintering conditions to yield high performance cathode active material. The Cu-Li2MnSiO4-PANI hybrid exhibits the reversible insertion of similar to 1.15 and 0.73 mol of Li for first and 50th cycles, respectively. This corresponds to the similar to 63% of retention. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: LI2MNSIO4; LI2FESIO4